Plasma and peritoneal fluid concentrations of ceftriaxone after intravenous and intraperitoneal administration in horses - Alonso, J. M. [UNESP]; Peccinini, R. G. [UNESP]; Campos, M. L. [UNESP]; Nitta, T. Y. [UNESP]; Akutagawa, T. Y.M. [UNESP]; Crescencio, A. P. [UNESP]; Alves, A. L.G. [UNESP]; Rodrigues, C. A. [UNESP]; Watanabe, M. J. [UNESP]; Hussni, C. A. [UNESP] (Elsevier, 2018)
Intraperitoneal (IP) use of antimicrobial agents may lead to therapeutic effects with better clinical results than intravenous (IV) administration. The aim of this study was to compare plasma and peritoneal fluid concentrations of ceftriaxone after IP and IV administration in horses, and to evaluate possible adverse effects. One group of five horses received 25 mg/kg ceftriaxone diluted in 1 L saline solution by IP catheter once daily for 5 days, while a second group of five horses received 25 mg/kg ceftriaxone diluted in 250 mL saline solution by IV injection once daily for 5 days and 1 L saline solution by IP catheter once daily for 5 days. Peritoneal fluid and plasma were collected to determine ceftriaxone concentrations after the first and fifth administration. IP administration of ceftriaxone resulted in concentrations above a minimum inhibitory concentration (MIC) of 1 μg/mL for 24 h in peritoneal fluid and for 12 h in plasma, while IV administration of ceftriaxone resulted in lower peritoneal fluid concentrations, which remained above a MIC of 1 μg/mL for 12 h in peritoneal fluid and 10 h in plasma. No adverse effects were observed. Comparisons of ceftriaxone concentrations, time of occurrence of the maximum (Tmax) and minimum (Tmin) concentrations, and the mean residence time (MRT), between the two groups showed that IP administration provided greater availability of cephalosporin in peritoneal fluid. The IP use of ceftriaxone (25 mg/kg diluted in 1 L saline solution once daily) may be useful for the prophylaxis and/or treatment of peritonitis in horses.
Keywords: Ceftriaxone; Equine; Intraperitoneal; Intravenous; Minimum inhibitory concentration